Does involvement of women in BRAC influence sex bias in intra-household food distribution? - Roy, Rita Das; Hyder, SM Ziauddin; Chowdhury, AMR; Adams, Alayne (BRAC Research and Evaluation Division (RED), 2019)
This study aimed to assess the sex preference in intra-household food distribution among school going siblings in a rural area of Bangladesh. The study also examines the effect of women's involvement in BRAC's rural development programme in reducing gender gaps in intrahousehold food allocation. The study was conducted in 14 villages of :Matlab thana as one of the sub-studies of the BRAC-ICDDR,B joint research project. A total of 376 school-going siblings (188 brothers and 188 sisters) aged 10-14 years from BRAC member and no~-member households were included in this study. Both quantitative and qualitative research methods were used for data collection. One of the villages was chosen for direct observation of food distnoution behaviour of the food servers. The methodology also included six focus group discussions with mothers of the siblings in two selected villages; this helped to have further understanding of the issue. The survey found no significant sex bias in food distribution for 3 major daily meals. However, boys were given preference in distributing special foods such as meat, fish and milk products. Brothers conswned higher amount of special foods compared to their sisters (p<0.001). Direct observation of food distribution and focus group discussions indicated that preferential food distribution pattern favouring sons, which existed in the rural community irrespective of social classes. It was also found that food was more equitably distributed between sons and daughters within BRAC member households compared to non-member households.